The central and peripheral structure of the social representation to the phenomenon of family maltreatment against children - Abidi, Sana (Journal of Human Sciences, 2022)
The education of the child has become difficult and so the family has lost its educational character by mistreating its children. Abuse takes many forms: corporal punishment that targets the child’s body, psychological abuse that threatens their moral security, sexual abuse through various types of harassment. Where we find parents who see the pattern of punishment as the optimal pattern in the formation of the child’s personality, then they use abuse. Therefore, this work aims to clarify the central and peripheral structure of the social representation of family maltreatment towards the child through the minds of a group of parents, and to achieve the objectives of the study we used the descriptive analytical method and the network of associations. We concluded that the axis of violence represents the central core in the structure of representation with its proximity to the axis of parenting methods, since it remains the preferred and common method of raising the child, the rest of the axes represent peripheral elements.